2013
DOI: 10.1007/s15010-013-0440-0
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide surveillance of antimicrobial consumption and resistance to Pseudomonas aeruginosa isolates at 203 Japanese hospitals in 2010

Abstract: This is the first national surveillance study of antimicrobial consumption in Japan. A continuous surveillance program in Japan is necessary in order to evaluate the association among resistance, antimicrobial restriction, and consumption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 22 publications
2
25
0
1
Order By: Relevance
“…Although viral infections account for the majority of pediatric respiratory infections, antimicrobials are often prescribed for these cases [8,9]. Previous surveys pointed out that the overprescription of oral cephalosporins and macrolides, which are usually prescribed for pediatric respiratory tract infections, is a serious issue in Japan [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Although viral infections account for the majority of pediatric respiratory infections, antimicrobials are often prescribed for these cases [8,9]. Previous surveys pointed out that the overprescription of oral cephalosporins and macrolides, which are usually prescribed for pediatric respiratory tract infections, is a serious issue in Japan [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…As the new powerful antibiotics, they are used only in intensive care unit (ICU). Linezolid and vancomycin keep very sensitive to S. aureus in our hospital as the last line therapeutic agents for many years to cure MRSA infections, though there were reports about the resistance to Linezolid and vancomycin in the world [8]. For the strict supervision, the susceptibility rate of nitrofurantoin and rifampin are over 90%, the susceptibility rate of moxifloxacin rised to 84.62%.…”
Section: Resultsmentioning
confidence: 88%
“…Skin and soft tissue infections caused by Staphylococcus aureus are commonly encountered [7], so the sputum and secretion/pus specimen accounts a large proportion. The antibiotic protocols suggested improve the proportion of the blood and other sterile site specimen as the basis for the choose antibiotics [8]. Because detecting the microorganism in blood is more accurate and helpful for the Doctor's diagnose than in sputum, though the sputum culture specimen is very easy to obtain.…”
Section: Resultsmentioning
confidence: 99%
“…Quinolones are widely used for the treatment of urinary tract infection, respiratory tract infection and other bacterial infections. Of all antimicrobial agents, the amount of quinolone use is the third highest after that of macrolides and β‐lactams . In particular, topical nadifloxacin and ozenoxacin and oral levofloxacin are used for treatment of skin diseases such as acne vulgaris .…”
Section: Introductionmentioning
confidence: 99%
“…Of all antimicrobial agents, the amount of quinolone use is the third highest after that of macrolides and b-lactams. 6 In particular, topical nadifloxacin and ozenoxacin and oral levofloxacin are used for treatment of skin diseases such as acne vulgaris. 7 We previously reported that the antimicrobial resistance of Cutibacterium (formerly Propionibacterium) acnes isolated from acne patients is affected by antimicrobial use.…”
Section: Introductionmentioning
confidence: 99%